The nervous system—A new territory being explored of SARS-CoV-2 - Zhang, Meng (J Clin Neurosci, 2020)
In December 2019, COVID-19 outbroke in Wuhan, then sweeping the mainland of China and the whole world rapidly. On March 4, Beijing Ditan Hospital confirmed the existence of SARS-CoV-2 in the cerebrospinal fluid by gene sequencing, indicating the neurotropic involvement of SARS-CoV-2. Meanwhile, neurological manifestations in the central nervous system, peripheral nervous system and skeletal muscular were also observed, indicating the potential neuroinvasion of SARS-CoV-2. In particular, we focused on its neurological manifestations and specific pathogenesis, as well as its comparison with other viral respiratory infections. Finally, we further summarized the significance of the neuroinvasion and the follow-up issues that need to be paid attention to by scientists, so as to help neurologists understand the influence of SARS-CoV-2 on nervous system better and promote the accurate diagnosis and efficient treatment of COVID-19.